Sociology, Ecology and a Global Economy - Marchak, Patricia (Cahiers de recherche sociologique, 1990)
SummaryThis paper presents the main approaches and issues of Anglo-canadian sociology of the last forty years, showing their limits and their theoretical inadequacies. It discusses the current practices of sociologists and asks the question: which social dimensions should be taken into account to strenghten sociological theory. It emphasizes the necessity to go beyond the framework of the social sciences to build a proper understanding of humanity and social activity.